2004
DOI: 10.1017/s0033291703008808
|View full text |Cite
|
Sign up to set email alerts
|

Does diagnosis determine delivery? The Islington study of older people's needs and health care costs

Abstract: Physical dependency significantly affects both health and social care costs. Increasing cognitive impairment mainly leads to increasing social care costs. Overall costs are increased by physical dependency, dementia, depression, subjective health problems, living alone and are negatively affected by being black.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Accordingly, a scale testing the affective status can be regarded as a surrogate measure of perceived health (Kennedy et al 2001). On the other hand, measures of cognitive ability and physical dependency were not correlated with the use of drugs, although they are well recognized indexes of health status impairment (Nelson et al 2004). This suggests an alternative explanation to the relationship between consumption of drugs and affective status: polypharmacy might negatively affect the perception of disease status (Fincke et al 1998) and, as a consequence, induce depression.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a scale testing the affective status can be regarded as a surrogate measure of perceived health (Kennedy et al 2001). On the other hand, measures of cognitive ability and physical dependency were not correlated with the use of drugs, although they are well recognized indexes of health status impairment (Nelson et al 2004). This suggests an alternative explanation to the relationship between consumption of drugs and affective status: polypharmacy might negatively affect the perception of disease status (Fincke et al 1998) and, as a consequence, induce depression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a person's living situation may affect the use of health care. Nelson et al 44 found that people who were 65 years of age or older and who were living alone were less likely to receive health care services. This finding may be attributable to an inability to access care outside the home.…”
Section: Outpatient Physical Therapy For Musculoskeletal Conditionsmentioning
confidence: 99%
“…Older adults living alone with cognitive impairment are at high risk for poor health outcomes [3]. They are less likely to use health services [4], and they are more exposed to self-neglect [5, 6] and falls [6] than counterparts living with others. Older adults living alone with cognitive impairment also report a higher number of unmet needs in managing money, medications, and mobility [6], and they are less likely to seek a diagnosis for their cognitive impairment [3, 7].…”
Section: Introductionmentioning
confidence: 99%